Fiscal rules and public investment - Eric Perée; Timo Välilä (European Investment Bank (EIB), 2005)
This paper examines the link between fiscal rules and public investment both normatively and empirically. We first review the arguments for and against including public investment spending in a fiscal deficit rule. We then seek to assess the determinants of public investment, with a special focus on the role of the fiscal rules embodied in EMU. We conclude that there are practical difficulties precluding the introduction of a 'golden rule' and that there is virtually no evidence that EMU would have affected public investment. Therefore, the focus on safeguarding the level of public investment is somewhat misplaced; instead, one should focus on safeguarding its productivity.
Keywords: E62; E65; H54; C23; 330